Outcome of Laparoscopic Versus Open Pyeloplasty in the Treatment of Pelviureteric Junction Obstruction: A Comparative Study (Bangladesh Journal of Urology, 2020)
Background: Ureteropelvic junction obstruction leads to progressive dilatation of the renal collecting system, and can result in pain and progressive deterioration of renal function but may be asymptomatic and result in complication such as pyelonephritis,calculus formation and deterioration of renal function may ensue if left untreated.Open pyeloplasty remains the gold standard against which new technique must be compared.we compared laparoscopic and open pyeloplasty in the treatment of pelviureteric junction obstruction. To see the outcome of laparoscopic pyeloplasty versus open A-H pyeloplasty in the management of pelviureteric junction obstruction.Methods and materials: A prospective quasi experimental study was done from july 2012 to December 2013 in which a total of 30 laparoscopic and 30 open pyeloplasty were done. All laparoscopic pyeloplasties were performed transperitoneally.Standard open A H pyeloplasty,spiral flap or VY plasty was done depending on anatomical consideration. Patients were followed with USG and IVU at three and six months interval.Perioperative parameters including operative time,analgesic use,hospital stay,and complication and success rates were compared.Results: Mean total operative time in LP group was 115±15 min compared to 75 ±15 in OP group, the postoperative analgesic requirement was sighnificantly less in LP group(mean 84.73±11mg) and OP group required mean of( 274.33±39.42mg).The mean blood loss in LP group was 118.26±110.74ml compared to open group 274.82±118.97ml.The postoperative hospital stay in LP was mean 4 days(2-7days) sighnificantly less than the open group mean of 8 days(7-9days).Conclusion: Lp has a minimal level of morbidity and short hospital stay compered to open approach.Although laparoscopic pyeloplasty has the disadvantages of longer operetive time and requires sighnificant skill of intracorporal knotting but it is here to stay and represents an emerging standard of care.Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.182-187